Starting an online business for dummies - Holden, Greg (For dummies, 2013)
Armed with a computer, an Internet connection, and a good idea-- but hesitant to take that first step toward making money online? Holden shows you want it takes to succeed in the world of e-commerce, and make your business dream a reality.